First Evidence from the Independent Expert Group to the Commission on Scottish Devolution - McLean, I; Aldridge, J; Bell, D; Darby, J (Heriot-Watt University, 2008)
Further authors: Sandra Eden, Charlie Jeffery, Anton Muscatelli, Jeremy Peat, David Ulph, Robin Boadway, Clemens Fuest and Andrew Hughes-Hallett